2020
DOI: 10.1080/15332640.2020.1725707
|View full text |Cite
|
Sign up to set email alerts
|

Childhood abuse, posttraumatic stress symptoms, and alcohol misuse among African-American women

Abstract: The study explored associations among childhood abuse, posttraumatic stress symptoms (PTSS), and alcohol misuse in a sample of low-income African American women (N = 172). Using bootstrapping techniques, a mediation effect was found of childhood physical and emotional abuse on alcohol misuse via PTSS symptom severity, avoidance, and hyperarousal, as well as for childhood sexual abuse on alcohol misuse via PTSS symptom severity and hyperarousal. Our results suggest that PTSS indicators, particularly symptom sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…However, Yuan et al, (2014) only found these associations in females. Contrary to the above, one study (Florez et al, 2020) found that CEA was not directly associated with alcohol misuse. Only two studies (Afifi et al, 2012;Elliott et al, 2014) explored the associations between CEN and substance abuse and found it significant.…”
Section: Cea and Cen And Adult Substance Abusementioning
confidence: 73%
“…However, Yuan et al, (2014) only found these associations in females. Contrary to the above, one study (Florez et al, 2020) found that CEA was not directly associated with alcohol misuse. Only two studies (Afifi et al, 2012;Elliott et al, 2014) explored the associations between CEN and substance abuse and found it significant.…”
Section: Cea and Cen And Adult Substance Abusementioning
confidence: 73%
“…In the completed review, 28 studies were dissected which consisted of qualitative and quantitative information. Of these studies, only 3 were specific to alcohol abuse (Florez et. al, 2022;Mulia, 2020;Verissimo et.…”
Section: Methodsmentioning
confidence: 99%
“…It has negative impacts on a wide range of mental health and behavioural outcomes, such as depression and anxiety [ 30 ], suicidality [ 4 ], and violence [ 27 ] [ 65 , 66 ]. However, a majority of past childhood maltreatment studies have focused on specific forms of childhood maltreatment and their links to mental health outcomes and there has been a relative lack of research on psychological maltreatment in particular [ 28 , 29 ]. Person-centred analyses, such as latent profile analyses, allow common exposure patterns to be identified among subgroups of participants [ 42 ].…”
Section: Introductionmentioning
confidence: 99%